Recognition of sentinel lymph nodes in patients with papillary thyroid cancer by nano-carbon and methylene blue - Liu, Fangzhou (Pak J Med Sci, 2017)
OBJECTIVE: To compare the accuracy and feasibility of methylene blue and nano-carbon in clinical tracing of sentinel lymph nodes (SLNs) in patients with papillary thyroid cancer (PTC). METHODS: Ninety-six PTC patients were selected and randomly divided into a methylene blue group and a nano-carbon group (n=48). During surgery, tracer agent was injected around the tumor, and SLNs were resected and subjected to frozen pathological examination. The results were compared with those of routine pathological examination after surgery. RESULTS: Latent lymph node metastasis (level VI and lateral neck) was detected in both groups, with neck distribution of SLNs. There was no significant difference in the detection rate or accuracy of SLNs between two groups (P>0.05). The incorrect resection rate of parathyroid gland and incidence of temporary hypoparathyroidism in the methylene blue group were significantly higher than those of the nano-carbon group (t=4.137, P<0.05). CONCLUSIONS: The state of PTC lymph nodes can be well evaluated by SLN biopsy using both methylene blue and nano-carbon as tracers, but using nano-carbon has a lower incidence rate of parathyroid injury, with great clinical prospects accordingly.